Correlations between elevated basal sperm DNA fragmentation and the clinical outcomes in women undergoing IUI - Zhu, Chunhui; Zhang, Shengmin; Chen, Fang; She, Hong; Ju, Yun; Wen, Xidong; Ji, Yurong; Pan, Yu; Yang, Chunxia; Sun, Yan; Dong, Naijun; Liu, Kaifeng; et al. (Frontiers in Endocrinology, 2022)
Abstract Objective: This study aimed to explore the impact of the sperm DNA fragmentation index (DFI) on the clinical outcome in women undergoing artificial insemination by husband intrauterine insemination (AIH-IUI) to evaluate the impact of sperm DNA fragmentation on clinical outcomes after IUI. Methods: In this study, the value of DFI was detected by sperm chromatin structure assay (SCSA) in a semen analysis collected before fertility treatment (baseline DFI) in 1500 IUI cycles at the infertility clinic of Northern Jiangsu People’s Hospital Reproductive Medicine Center from Jan 2016 to April 2021. Receiver operating characteristic (ROC) curves were used to calculate the cut-off value for the clinical outcomes of IUI, and multivariate logistic regression was conducted to analyse the risk factors for clinical outcomes after IUI. Result: In 1500 insemination cycles, the results showed that there were no statistically significant differences between the normal DFI group and the abnormal DFI group in biochemical pregnancy rate (14.41% vs. 11.3%, P = 0.386), clinical pregnancy rate (12.9% vs. 10.5%, P = 0.433), delivery rate (11.0% vs. 8.9%, P = 0.456), live birth rate (10.9% vs. 8.9%，P = 0.484) or abortion rate (15.4% vs. 14.6%, P = 1.000). Conclusion: Sperm DFI alone may have limited predictive power for IUI clinical outcomes.